Emerging the Dark Sector from Thermodynamics of Cosmological Systems with Constant Pressure - Cruz-Marin, N (Springer New York LLC, 2015)
We investigate the thermodynamics of general fluids that have the constriction that their pressure is constant. We first consider the more general thermodynamic properties of this class of fluids finding the important result that for them adiabatic and isothermal processes should coincide. We therefore study their behaviors in curved space-times where local thermal equilibrium can be appealed. Thus, we show that this dark fluid degenerates with the dark sector of the $$\Lambda $$ΛCDM model only in the case of adiabatic evolution. We demonstrate that, adding dissipative processes, a phantom behavior can occur and finally we further highlight that an arbitrary decomposition of the dark sector, into ad hoc dark matter and dark energy terms, may give rise to phantom dark energy, whereas the whole dark sector remains non-phantom. © 2015, Springer Science+Business Media New York.